Differential Effects of Variable Frequencies of Manual Acupuncture at St36 in Rats with Atropine-Induced Inhibition of Gastric Motility. Issue 1 (February 2016) - Gao, Li-Li; Guo, Yi; Sha, Tao; Liu, Yang-Yang; Tang, Jia-Bei; Yuan, Fang; Zhou, Tao; Hong, Shou-Hai; Ming, Dong
Objective: The 'intensity-response' relationship between acupuncture stimulation and therapeutic effect is currently the focus of much research interest. The same needling manipulation with different frequencies can generate differential levels of stimulus. This study aimed to examine the effects on gastric motility induced by four twirling frequencies based on relatively standardised manual acupuncture (MA) manipulations. Methods: Twirling manipulations at 1, 2, 3, and 4 Hz were practised before the experiments by a single operator using an MA parameter measurement device and stability was evaluated through time-frequency analysis. Forty-eight Sprague-Dawley rats were randomly divided into six groups (n=8 each): Control, Model, Model+MA (1, 2, 3, and 4 Hz). Rats in the five Model groups received injections of atropine into the tail vein to inhibit gastric motility, which was continuously recorded by a balloon in the gastric antrum. Rats in the four Model+MA groups received MA at 1, 2, 3 and 4 Hz, respectively, for 70 s and needles were retained for a further 5 min. Results: The amplitude of waveforms produced by the four twirling frequencies was relatively consistent and reproducible. The gastric motility amplitude in all groups decreased after modelling (injections of atropine) (p<0.01). Twirling manipulation at 1, 2, and 3 Hz (but not 4 Hz) increased gastric motility amplitude (p<0.05). The increase in gastric motility amplitude induced by MA at 2 Hz was greater than for all other frequencies (p<0.05). Conclusions: Acupuncture at ST36 helped recover gastric motility amplitude in rats with atropine-induced gastric inhibition and the effects induced by 1–3 Hz frequency were greater than those induced by 4 Hz.